A new garden eel, Heteroconger fugax (Congridae: Heterocongrinae), from the northwestern Pacific Ocean - Koeda, Keita; Fujii, Takuma; Motomura, Hiroyuki (Zootaxa, 2018)
Heteroconger fugax sp. nov. (Congridae: Heterocongrinae) is described from a single specimen collected from Amami-oshima island, Japan. The new species is most similar to Heteroconger tomberua Castle & Randall 1999, known from Fiji and New Caledonia, in having a remarkably slender body with numerous small spots and a vertebral count close to 200. However, it can be distinguished from H. tomberua by the presence of a large distinct white blotch on the opercle; more numerous, dense spots over the entire head, including lips; ground color of body uniformly cream, without microscopic melanophores; numerous small conical cirri on the chin; and dorsal-fin origin located more posteriorly to appressed pectoral-fin tip. A survey of underwater photographs of Heteroconger on photographic database revealed H. fugax to be widely distributed in the northwestern Pacific Ocean, from the Ryukyu Archipelago to Borneo.